A 360° perspective of women in soil science focused on the U.S - Grunwald, Sabine; Daroub, Samira (Frontiers in Soil Science, 2023)
Gender parity and equity concerns in soil science have been reported in the United States and at global scale. Long-standing biases and gender stereotypes have discouraged women away from science, technology, engineering, and mathematics (STEM) research in particular soil science. However, it has been recognized that science and gender equality are essential to ensure sustainable development as highlighted by the United Nations Educational, Scientific and Cultural Organization (UNESCO). Gender equity is part of diversity, equity, and inclusivity (DEI) initiatives in higher education and professional soil science organizations in the U.S. and elsewhere. In this article we aim to provide a holistic 360° perspective of women and soils addressing gender parity, equality, and equity in the soil science profession. Our critical analysis is grounded in Integral theory that considers 1) systemic institutional, organizational, educational, legal, social, political, and other system phenomena (collective perspective), 2) historical and cultural phenomena such as people’s values, beliefs, motivations, communications, traditions, memes, morals, and ethics (interpersonal perspective), and 3) individual psycho-spiritual attitudes, stories, personal voices, emotions, and experiences (subjective intrapersonal perspective). This paper provides a critical review of the issues and barriers confronting women researchers, teachers, and professionals in soil science in the U.S. and around the globe. Concluding remarks present future perspectives of women and soils that include leadership training, mentoring for change, personal development of women soil scientists, and participation that co-creates gender parity, equity, and equality in the soil science profession.